Dominant species' resprout biomass dynamics after cutting in the Sudanian savanna-woodlands of West Africa: long term effects of annual early fire and grazing - Dayamba, Sidzabda Djibril; Savadogo, P.; Sawadogo, L.; Zida, D.; Tiveau, D.; Oden, P.C. (2011)
The potential of forest to regenerate after harvesting is a key element for sustainability of the ecosystem. For semi-arid tropical savanna environments, managing resprouts after tree cutting is ideally suited because of the natural ability of many indigenous species to regenerate vegetatively. Regeneration in this ecosystem is, however, prone to many disturbance factors such as fire and grazing by livestock. In this paper, we used a factorial experiment to examine the long-term effects of annual early burning and grazing on dominant species' resprout biomass dynamics after selective cutting in the Sudanian savanna-woodlands of Burkina Faso, West Africa Burning decreased shoot mortality of Crossopteryx febrifuga while grazing increased that of Detarium microcarpum. Burning, in later measurement years, reduced resprouts' size of Acacia macrostachya, C. febrifuga and D. microcarpum while an increased basal area was observed for Combretum glutinosum. There was no significant evidence of grazing hampering growth. Moderate livestock grazing could be integrated in the forest management prescriptions in Burkina Faso for the sake of multi-purpose uses, while more attention should be paid to burning practices to lower fire severity, as complete fire exclusion is utopian in this savanna ecosystem.